2014
DOI: 10.3126/hren.v11i3.9637
|View full text |Cite
|
Sign up to set email alerts
|

Lip print pattern: an identification tool

Abstract: Background: Cheiloscopy is a forensic investigation technique that deals with the identification based on lip traces. Based upon the research, it was established that the arrangement of lines on the red part of human lips is unique for each human being. Objectives: To analyze and compare quadrant wise and sex wise predilection of lip print pattern. Methods: A total of 200 (18-25 years) Nepalese undergraduate students of BPKIHS were selected. Thin layer of lip-stick was applied on the lips of these sub-jects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 6 publications
3
20
2
Order By: Relevance
“…Likewise, studies conducted in Nepal also revealed Type I and II as the most and least common in male and female respectively. 17 But, in our study, even in female, the Type I (29.7%) was still the most common, followed by Type I' (25%), Type II (23.4%), Type IV (9.4%), Type III (7.8%) and Type V (4.7%).…”
Section: 2%contrasting
confidence: 57%
See 2 more Smart Citations
“…Likewise, studies conducted in Nepal also revealed Type I and II as the most and least common in male and female respectively. 17 But, in our study, even in female, the Type I (29.7%) was still the most common, followed by Type I' (25%), Type II (23.4%), Type IV (9.4%), Type III (7.8%) and Type V (4.7%).…”
Section: 2%contrasting
confidence: 57%
“…However, Type I was still the most common in both sexes in this quadrant too. 17 in comparison to a study where to Type II (4%, 10%) was the least and Type III (50%, 38%), the most common in both male and female respectively. 13 In right lower quadrant (RLQ), Type II (31.2%) was the predominating, following which were Type I (30.5%), Type III (21.3%), Type I' (7.1%), Type IV (6.4%) and Type V (3.5%) in male and Type I (42.2%),Type II (25%), Type I' (17.2%), Type III (9.4%), Type IV (4.7%) and Type V (1.6%) in female.…”
Section: 2%mentioning
confidence: 53%
See 1 more Smart Citation
“…Suzuki and Tsuchihashi classifications was selected for this research because it was widely used classification in literature [4]. Figure 1 shows six types of lip prints based on its shape and type of grooves in Suzuki and Tsuchihashi classification [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lip prints are considered to be a new method that can adjudicate personal identification in criminal search and genetic studies [2]. Fingerprints and lip prints are permanent and inalterable over time unless there is a pathology which can affect the lips and fingers [3,4]. Cheiloscopy can also be used in gender and races determination [5].…”
Section: Introductionmentioning
confidence: 99%